Pengaruh Content Marketing di Instagram Growthspace.id terhadap Minat Beli Webinar Growth Space - Sari, Debbie Permata; Valdez, Mohamad Alppy (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2023)
The digital era has positioned content marketing as a paramount strategy in attracting consumer interest. This study focuses on how Content Marketing on Instagram Growthspace.id impacts the Purchase Interest of Growth Space webinars. A qualitative approach was applied in this research involving 100 respondents through purposive sampling techniques. Seven dimensions, namely Relevance, Informative, Reliability, Value, Uniqueness, Emotion, and Intelligence are used to assess content marketing, while six dimensions, namely Awareness, Knowledge, Liking, Preference, Conviction, and Purchase are utilized to measure purchase interest. The results show the significance of content marketing strategies, with an influence of 56.1% on the interest in purchasing webinars. This finding signifies the power of content marketing in driving webinar sales.